Strengthening Student Character Education Through the Digital Literacy Movement in Supporting Society 5.0 - Utami, Dian Tri; Nisa, Ana Fitrotun; Kurniastuti,; Utami, Ika Wati Tresna (International Conference on Elementary Education, 2025)
In the society 5.0 era, digital technology not only accelerates innovation, but also plays a key role in shaping the character and mindset of the younger generation. Digital literacy is an important foundation in creating individuals who are adaptive, critical and globally competitive. This research aims to describe strengthening character education through digital literacy implemented in elementary schools. The method used is qualitative descriptive This research method is qualitative descriptive research with stages of data collection, data reduction, data display and conclusion drawing. Data collection techniques use observation, interviews and documentation techniques. While the data analysis technique uses qualitative descriptive techniques. The results of this research show that the digital literacy movement can help strengthen characters such as critical reasoning, creativity and independence. Digital literacy, which involves using technology wisely and responsibly, is very important in supporting character education. Additionally, the integration of technology in education can help students develop moral values, digital ethics, and critical skills. Obstacles such as limited infrastructure and insufficient teacher knowledge can be overcome with training and government policy support. This research recommends the importance of digital literacy training for teachers, developing a digital literacy- based curriculum, and improving technology infrastructure in schools.